Factors Affecting Weight Gain for Pregnant Women at the Ketapang II Sampit Health Center, East Kotawaringin Regency, Province Central Kalimantan - Wulandari, Anggrawati; Siti Marfuatun Hasanah (Master of Public Health Program Universitas STRADA Indonesia, 2023)
Lack of knowledge about nutrition during pregnancy, wrong diet causes the risk of chronic energy deficiency which has an impact on pregnant women's weight loss. The purpose of this study was to analyze the factors that influence the weight gain of pregnant women at the Ketapang II Sampit Health Center, Kotawaringin Timur Regency, Central Kalimantan Province.The design of this study is an observational analytic with a cross sectional approach. Respondents were taken by purposive sampling technique that met the inclusion and exclusion criteria with a sample of 30 people. The independent variables are knowledge, diet, chronic energy deficiency and the dependent variable is the weight gain of pregnant women. Statistical test results using Logistic Regression.The results showed that most of the respondents 18 (60%) had good knowledge, eating patterns were known by half of the respondents 15 (50%) in the good category, chronic energy deficiency was known by most of the respondents 22 (73%) that CED did not occur, weight gain in pregnant women was known by almost all respondents 23 (77%) in the appropriate category.The results of data analysis showed that the knowledge variable had a significance level (0.003), eating pattern variable (0.005), Chronic Energy Deficiency (KEK) variable (0.008). Thus it can be concluded that there is an effect of knowledge, diet and chronic energy deficiency on weight gain of pregnant women at the Ketapang II Sampit Health Center, East Kotawaringin Regency, Central Kalimantan Province.Based on the results of the study it was concluded that the better the knowledge about chronic energy deficiency, the better the diet, the mother's weight will increase according to gestational age.